Trends and drivers of change in the prevalence of anaemia among 1 million women and children in India, 2006 to 2016 - Nguyen, Phuong Hong; Scott, Samuel P.; Avula, Rasmi; Tran, Lan Mai; Menon, Purnima (BMJ, 2018)
India carries the largest burden of anaemia globally. Progress to reduce anaemia has been slow despite substantial economic growth and 50 years of programmatic efforts. Identification of the factors that contribute to anaemia reductions is needed to accelerate progress. We examined changes in haemoglobin (Hb) and anaemia among women and children in India from 2006 to 2016 and identified drivers of changes in these outcomes over time.